The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4103/0971-3026.190406
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in spinal posterior epidural space lesions: A pictorial essay

Abstract: Spinal epidural space is a real anatomic space located outside the dura mater and within the spinal canal extending from foramen magnum to sacrum. Important contents of this space are epidural fat, spinal nerves, epidural veins and arteries. Due to close proximity of posterior epidural space to spinal cord and spinal nerves, the lesions present with symptoms of radiculopathy and/or myelopathy. In this pictorial essay, detailed anatomy of the posterior epidural space, pathologies affecting it along with imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 51 publications
1
36
0
Order By: Relevance
“…1 After the introduction of MRI the incidence and number of diagnosed have further increased. [5][6][7] A spinal epidural hematoma can occur in the absence of any trauma or iatrogenic procedures. This definition also includes causes, such as a tumor, coagulopathy, vascular malformation, and cavernous angioma.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…1 After the introduction of MRI the incidence and number of diagnosed have further increased. [5][6][7] A spinal epidural hematoma can occur in the absence of any trauma or iatrogenic procedures. This definition also includes causes, such as a tumor, coagulopathy, vascular malformation, and cavernous angioma.…”
Section: Discussionmentioning
confidence: 99%
“…This definition also includes causes, such as a tumor, coagulopathy, vascular malformation, and cavernous angioma. 1,2,4,7 The age of patients has bimodal peaks, with an increase in the second and seventh decades. 7 Halim et al 10 demonstrated that there is no significant correlation with sex and race.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations